(3GdSGHb hGddGMb aj JHGYO eGHjf GdQGhjjf Yf TjN hGMOs - (3GdNWjH GdHZOGOj , CMeO Hf Ydj Hf KGHJ , CHh HcQ , J (B463 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjN GdEeGe GdYGde CHheMeO YHOGddg Hf CMeO GdNTGH QMeg Gddg bQGAI Ydjg hPdc SfI (B566 s
(3BNQgG (B:s
(3JfJgj YfO CSe(B: (3jYbhH Hf EHQGgje GdOhQbj s
(3JHUQI GdYfhGf (B:s
(3QhGjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B172 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B3s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B81 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs